Glucagon kinetics assessed by mathematical modelling during oral glucose administration in people spanning from normal glucose tolerance to type 2 diabetes - Andreozzi, Francesco; Mancuso, Elettra; Rubino, Mariangela; Salvatori, Benedetta; Morettini, Micaela; Monea, Giuseppe; Göbl, Christian; Mannino, Gaia Chiara; Tura, Andrea (Frontiers in Endocrinology, 2024)
Background/Objectives Glucagon is important in the maintenance of glucose homeostasis, with also effects on lipids. In this study, we aimed to apply a recently developed model of glucagon kinetics to determine the sensitivity of glucagon variations (especially, glucagon inhibition) to insulin levels (“alpha-cell insulin sensitivity”), during oral glucose administration. Subjects/Methods We studied 50 participants (spanning from normal glucose tolerance to type 2 diabetes) undergoing frequently sampled 5-hr oral glucose tolerance test (OGTT). The alpha-cell insulin sensitivity and the glucagon kinetics were assessed by a mathematical model that we developed previously. Results The alpha-cell insulin sensitivity parameter (named SGLUCA; “GLUCA”: “glucagon”) was remarkably variable among participants (CV=221%). SGLUCA was found inversely correlated with the mean glycemic values, as well as with 2-hr glycemia of the OGTT. When stratifying participants into two groups (normal glucose tolerance, NGT, N=28, and impaired glucose regulation/type 2 diabetes, IGR_T2D, N=22), we found that SGLUCA was lower in the latter (1.50 ± 0.50·10-2vs. 0.26 ± 0.14·10-2 ng·L-1GLUCA/pmol·L-1INS, in NGT and IGR_T2D, respectively, p=0.009; “INS”: “insulin”). Conclusions The alpha-cell insulin sensitivity is highly variable among subjects, and it is different in groups at different glucose tolerance. This may be relevant for defining personalized treatment schemes, in terms of dietary prescriptions but also for treatments with glucagon-related agents.